A política de cotas raciais no curso de elevado perfil socioeconômico da Universidade Federal : a inclusão através da visão dos docentes e discentes - Graeff, Betina Alves (2020)
The present research studies the policy of affirmative action with black quota students, medical school students, at the Federal University of Rio Grande do Sul. The objective is to discuss the constitution of the quota policy directed at blacks, graduates of public schools, who entered the higher socioeconomic profile course at the Federal University of Rio Grande do Sul, in the years 2008 to 2018. It is understood that the training of black quota students is extremely important, since they are part of a group historically placed on the margins of Brazilian society since its colonization. The admission through quotas may or may not allow self-declared black quota students to have the opportunity to be protagonists of their own lives as they will have the opportunity to reach, after graduation, positions of greater prominence in Brazilian society. The research is of a qualitative nature. The participating subjects are teachers and students, and the information was collected through a non-identifiable online questionnaire. Content analysis was used to unveil the information collected, as well as to guide the understanding of the documents, laws and bibliographies worked on. The listed authors have critical theories and concepts about the theme and are basically from three areas: education, social work and law. Among the results, the following stand out: The PAA within UFRGS in the medical course has been effective as a promoter of inclusion of PPIs students having revealed a low level of dropout and a high level of graduation in the segment. On the other hand, the conceptions about PAA, in the view of teachers, are charged with conservatism and ignorance about the substantial equality and the historical debts that Brazilian society has with Afro-descendants. It bluntly demonstrated the contradiction between the inclusion and the conformation of the PAA that presented itself in the academic trajectory of students, institutional racism, racism and prejudice.